Performance of Urea-Based Enhanced Efficiency Fertilizers Under Sidedress Nitrogen Placement Methods - Nutifafa Adotey; Angela T. McClure; Xinhua Yin; Jacob P. McNeal; Andrew B. Denton (Agronomy)
Enhanced efficiency nitrogen fertilizer (EENF) is a viable N management tool that can minimize N loss and maximize crop productivity. Research on the efficiency of EENF under relatively newer N-sidedress placement methods for liquid fertilizers, such as Y-Drop dribble, is limited, hence the necessity to address this knowledge gap. A two-year field trial was conducted to evaluate ammonia volatilization, grain quality, and grain yield from surface-applied EENF forms of urea and EENF forms of urea ammonium nitrate (UAN) applied under four placement methods in a rainfed no-till corn production system. The EENF forms of urea evaluated in this trial included Environmentally Smart Nitrogen, SuperU, and ANVOL-treated urea, while ANVOL-treated UAN was the EENF form of UAN. All the urea fertilizers were surface broadcasted while the UAN fertilizers were broadcasted, dribbled in between rows, Y-Drop dribbled, and injected behind colters. Among the non-EENF, urea volatilized the most ammonia (23.1% of total N applied) compared to UAN. Broadcast UAN was much more susceptible to ammonia volatilization than dribbled UAN in between rows. In this trial, the EENF forms of urea and UAN reduced ammonia loss by 65 to 94 and 50 to 51%, respectively, compared to their corresponding non-EENF forms. In 2021, the grain yield of the non-EENF forms of UAN was similar to the EENF forms of the corresponding placement methods. In contrast, there was an additive yield effect from all the urea forms of EENF. A significant negative relationship was observed between ammonia loss and grain protein, grain N, and grain yield; hence, placement methods with higher ammonia loss potential are prone to yield loss.